The turtle carapace as an optimized multi-scale biological composite armor – A review. (September 2017) - Achrai, Ben; Wagner, H. Daniel
Abstract: The turtle carapace, the top dorsal part of the shell, is a remarkable multi-scale dermal armor that has evolved to withstand various types of high-stress events encountered in nature. This keratin-covered boney exoskeleton exhibits a number of structural motifs, including alternating rigid and flexible components, layering and functionally graded elements, designed to protect the reptile during predatory attacks, and smashing events. Here we review the multi-scale structural hierarchy of the turtle carapace and its corresponding mechanical properties. We show how the microscopic features of the carapace govern its various macroscopic mechanical responses relevant to protective functioning, including dynamic (impact and cyclic) compression and bending loading situations. In addition, the effect of hydration, a crucial factor for proper physiological-mechanical behavior of biological materials, is illustrated throughout. We also discuss carapace-inspired designs that could be advantageous over the traditional strategies adopted in impact-resistant materials, and could bring new mechanistic insights. Graphical abstract: